Movies, positive psychology and body resilience: Overcoming for happiness - Fortunato, Ivan; Schwartz, Gisele Maria [UNESP] (Universidade Estadual de Maringa, 2019)
This paper deals with an investigation centered on the human relationship with the movies, from a Positive Psychology point of view, which focuses on the promotion of values and well-being. This search emerges from the following question: could movies potentiate the confrontation to overcome strong contingent adversities to human life? Specifically, the purpose of the paper is to discuss how movies can enhance the body resilience. Therefore, the sense of resilience is explored when the body itself seems to limit someone to perform ordinary tasks. For that, the movies Meu pé esquerdo (1989) and A teoria de tudo (2014), which portray, respectively, the stories of Christy Brown and Stephen Hawking are both used as clear examples that the limitation of the body is not enough to limit the happiness. In the end, the elements identified in the selected narratives are expected to help strengthen movies as foundational technology for human development, especially from the perspective of Positive Psychology.
Cinema, psicologia positiva e a resiliência do corpo: Superar para a felicidade
Keywords: Movies; Positive psychology; Resilience